Menghadirkan Kesejahteraan Berbasis Rumah Tuhan: Penyuluhan Moderasi Beragama bagi Tokoh Lintas Agama Kemenag Bone bolango - Supandi Rahman (Scimadly Publishing, 2022)
In fact, there is no religion on earth that loves poverty. Religions must unite to direct all available resources to combat socio-economic inequality. Because the biggest obstacle to the religious moderation program is poverty and poverty is one of the main routes for acts of extremism. This is where the importance of the implementation of religious moderation counseling for actors of religious harmony in the Office of the Ministry of Religion of Bone Bolango Regency with the theme